Added value of dual-phase 99mTc-HYNIC-FAPI-04 SPECT/CT in postoperative follow-up of colorectal cancer - Sun, Donghua; Liu, Yan; Hou, Renhua; Li, Jianan; Peng, Ye; Wang, Yingqiu (Frontiers in Oncology, 2025)
ObjectiveTo assess the added value of dual-phase 99mTc-HYNIC-FAPI-04 single-photon emission computed tomography/computed tomography (SPECT/CT) compared with single-phase imaging in postoperative follow-up of colorectal cancer (CRC).MethodsEarly and delayed 99mTc-HYNIC-FAPI-04 SPECT/CT imaging were undertaken in 21 patients with CRC after surgery. The mean radioactivity count of the lesion site and abdominal aorta in secondary imaging was delineated and measured. The early and delayed target background ratio (TBR) and retention index (RI) were calculated, respectively. The results of biopsy or postoperative pathology, clinical and imaging follow-up were used as the “gold standard” of tumor metastasis. Lesions were divided into “benign” and “malignant” groups. The uptake rate and metabolic rate of 99mTc-HYNIC-FAPI-04 in the two groups were observed. The diagnostic efficiency of early imaging, delayed imaging, and their combination for prediction of benign and malignant lesions was compared using receiver operating characteristic (ROC) curves.ResultsFifty-five lesions with abnormal uptake of 99mTc-HYNIC-FAPI-04 were found by SPECT/CT. Compared with TBR-early, TBR-delayed in malignant group was increased (4.07 ± 1.65 vs. 4.36 ± 1.86, P = 0.040), whereas TBR-delayed in the benign group was decreased significantly (2.96 ± 0.85 vs. 2.66 ± 0.77, P < 0.001). The mean count of radioactivity in the delayed phase, TBR-early, TBR-delayed, and RI in the malignant group were higher than those in the benign group (P = 0.005, <0.001, and <0.001, respectively). ROC curves showed that combined application of TBR-early, TBR-delayed, and RI had an AUC of 0.889, specificity of 0.900, and sensitivity of 0.844, and its diagnostic efficiency was superior to that of TBR-delayed (P = 0.026) and TBR-early (P <0.001).ConclusionsDual-phase 99mTc-HYNIC-FAPI-04 SPECT/CT could be used for the detection of metastatic lesions after CRC surgery. It has a higher auxiliary role than single-phase imaging for the differential diagnosis of benign and malignant lesions after CRC surgery.